Os idosos em situaç\~ao de dependência e a proteç\~ao social no Brasil - Analia Soria Batista; Luciana Jaccoud; Luseni Aquino; Patrícia Dario El- Moor (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– Functional dependency in elderly people has been studied in many countries where demographic changes have led to the increase in the over 60 age group. In Brazil, it has aroused interest of public agents and society due to the appearance of specific demands related to personal, domestic and medical long term care. Aiming to contribute to the debate regarding the provision of social protection to this public, this text presents an overview of the social situation of aged people and dependent/frail elderly in Brazil, as well as a short analyses concerning the benefits and services offered by the Brazilian social security system. Finally, the document discusses some of the challenges that this new phenomenon brings up to public policy.
Keywords: I38; J14; 330